Use of social media by part-time students of the polytechnic Ibadan, Oyo State, Nigeria (2018)
Social media provides the avenue for communication and interaction among students and lecturers using multimedia features such as texts, pictures and videos. Despite the benefits associated with the use of the social media, it seems most students use social media mostly for various purposes other than academic activities. The main objective of this study is therefore, to find out the use of social media for academic purpose among part-time students in the Polytechnic Ibadan. A sample of 213 year one part-time National Diploma (ND) students was selected and data were collected using a questionnaire. Results revealed that Facebook was the most available and the most used social media for academic purpose. Majority of the students chose learning and assignment as the academic activities that necessitated their use of social media. Erratic power supply of electricity and high cost of subscription to internet data bundle were the major challenges encountered by the students. Recommendations based on the outcome of this study were highlighted in this study.